Effect of Nozzle Type on Combustion Characteristics of Ammonium Dinitramide-Based Energetic Propellant - Jianhui Han; Luyun Jiang; Jifei Ye; Junling Song; Haichao Cui; Baosheng Du; Gaoping Feng (Aerospace)
The present study explores the influence of diverse nozzle geometries on the combustion characteristics of ADN-based energetic propellants. The pressure contour maps reveal a rapid initial increase in the average pressure of ADN-based propellants across the three different nozzles. Subsequently, the pressure tapers off gradually as time elapses. Notably, during the crucial initial period of 0–5 μs, the straight nozzle exhibited the most significant pressure surge at 30.2%, substantially outperforming the divergent (6.67%) and combined nozzles (15.5%). The combustion product variation curves indicate that the contents of reactants ADN and CH3OH underwent a steep decline, whereas the product N2O displayed a biphasic behavior, initially rising and subsequently declining. In contrast, the CO2 concentration remained on a steady ascent throughout the entire combustion process, which concluded within 10 μs. Our findings suggest that the straight nozzle facilitated the more expeditious generation of high-temperature and high-pressure combustion gases for ADN-based propellants, expediting reaction kinetics and enhancing combustion efficiency. This is attributed to the reduced intermittent interactions between the nozzle wall and shock waves, which are encountered in the divergent and combined nozzles. In conclusion, the superior combustion characteristics of ADN-based propellants in the straight nozzle, compared to the divergent and combined nozzles, underscore its potential in informing the design of advanced propulsion systems and guiding the development of innovative energetic propellants.